2014
DOI: 10.1590/0103-0582201432212113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of headache and its interference in the activities of daily living in female adolescent students

Abstract: OBJECTIVE: To describe the prevalence of headache and its interference in the activities of daily living (ADL) in female adolescent students. METHODS: This descriptive cross-sectional study enrolled 228 female adolescents from a public school in the city of Petrolina, Pernambuco, Northeast Brazil, aged ten to 19 years. A self-administered structured questionnaire about socio-demographic characteristics, occurrence of headache and its characteristics was employed. Headaches were classified according to the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
(80 reference statements)
3
26
0
3
Order By: Relevance
“…Similarly, those using computers for work or leisure for more than three hours have 70% more chances of presenting headache. This reality is not different in Brazil where current studies show high prevalence of headache among adolescents, with decreased quality of life 10,11 , negative impact on daily activities 12 as well as on academic performance 11 . Brazilian technological development, both in job market and social communications, requires the mastering of electronic devices, regardless of socio-economic conditions.…”
Section: Introductionmentioning
confidence: 73%
“…Similarly, those using computers for work or leisure for more than three hours have 70% more chances of presenting headache. This reality is not different in Brazil where current studies show high prevalence of headache among adolescents, with decreased quality of life 10,11 , negative impact on daily activities 12 as well as on academic performance 11 . Brazilian technological development, both in job market and social communications, requires the mastering of electronic devices, regardless of socio-economic conditions.…”
Section: Introductionmentioning
confidence: 73%
“…Similarly in this study headache was the top first condition that prompted self-medication and hence analgesics were the mostly used drugs. Another study showed that headache is highly prevalent (as high as 87.7%) among university students [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Less than half of the adolescents in this study take medication to relieve headaches. Considering that the overuse of headache medication is believed to worsen headaches.…”
Section: Self-medicationmentioning
confidence: 97%
“…It is important to inform the population about the consequences of frequent use of non-prescribed headache medications. 39 Children with headache are at a higher risk of experiencing recurring headaches during adulthood; accordingly, strategies for coping with psychosocial adversity in childhood may improve the prognosis in adulthood. 24 Therefore a healthy lifestyle including regular physical exercise, may improve headaches in children and adolescents.…”
Section: Self-medicationmentioning
confidence: 99%